Supratentorial extra-axial ependymoma: a case report and review of the literature - Salazar Analuisa, Jonathan Gabriel; Carballo, Leandro; Echavarría Demichelis, Mickaela (Revista Argentina de Neurocirugía, 2026)
Background: ependymomas are central nervous system tumors that occur most frequently in the pediatric population, typically in an infratentorial location. Among supratentorial ependymomas, the most common site is the ventricular ependyma. Extraventricular ependymomas are rare and usually located near the ventricles. Even rarer are extraventricular ependymomas that arise independently of the ventricular ependyma, with only a handful of cases reported in medical literature. Objective: to describe a case of extra-axial supratentorial ependymoma in an adult, a rare entity with very limited documentation in literature. Case description: we report the case of a 32-year-old woman with a history of seizures. Brain MRI revealed a large extra-axial lesion in the left frontal region producing a mass effect, for which surgical resection was scheduled. Surgery: total resection of the lesion was performed through a wide left fronto-temporo-parietal Penfield approach. Histopathology revealed a glial-lineage neoplastic proliferation composed of cells with spherical nuclei and fibrillar cytoplasm. A clear cell component was observed, along with predominant ependymal pseudorosette-like structures and focal papillary transformation. EMA immunostaining showed strong paranuclear dot-like positivity, while GFAP demonstrated diffuse intense positivity in all tumor elements. Conclusions: extra-axial supratentorial ependymomas are exceedingly rare. Surgical resection remains the first-line treatment to confirm the diagnosis and thus develop subsequent oncologic treatment.